Elements of Arabic Rhetoric in Dialogue between Parents and Children in the Quran - Zakaria, Muhammad Fadhlurrahman; Hardin, Nurul Isra; Aziz, Husein (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
This study aims to understand the concept of rhetoric and analyze the elements of different studies related to it. Emphasis is also placed on the style of dialogue in the Qur'an and the rhetorical elements used in the dialogue between parents and children. Particular attention is paid to the style of dialogue between parents and children, focusing on the aesthetic and technical aspects of rhetoric in this context. Research objectives are set to uncover the aesthetics of the Qur'anic style of discourse and to understand the beauty of expression between fathers and sons. This research is categorized as library research, as it addresses the elements of rhetoric in the dialogue between parents and children. Based on this research, the researcher developed two formulations: What are the verses in the Qur'an that contain dialogue between parents and children, and how to describe the types of rhetorical elements found in the dialogue between parents and children. Based on this formulation, the researcher found the most dialogues, but the researcher discovered four dialogues between fathers and their sons, namely: Noah's dialogue with his son, Jacob's dialogue with his son, Luqman's dialogue with his son, and Abraham's dialogue with his son. Some rhetorical elements were found, by understanding the arts of statement, semantics, and badiya within these dialogues.